Ecological Determinants of Pathogenic Leptospira Survival: Microbial Interactions, Environmental Stressors, and One Health Perspectives - Robby Wijayanto; Zilfiarani, Chalida Nahendra; Fahlefi, Moch. Ilham Riza (Universitas Airlangga, 2026)
Leptospirosis is a significant zoonotic disease that remains highly endemic in tropical and subtropical regions. The pathogenic Leptospira spp. can persist for extended periods in both aquatic and terrestrial environments, posing a long-term threat to public health. However, most studies have focused on pathogenesis and host-pathogen interactions. The ecological and microbial components were examined. This review explores the ecological determinants of Leptospira survival, emphasizing microbial interactions and their relevance within the One Health framework. Leptospira persistence is influenced by abiotic stressors (temperature, pH, moisture, and soil minerals), biotic interactions (such as co-aggregation with other bacteria, protozoan predation, and bacteriophage activity), and anthropogenic factors including deforestation, agricultural intensification, and urbanization. Evidence shows that Leptospira survive best under high humidity, neutral to alkaline pH, and moderate temperatures, while extreme stressors such as drought, high temperature, or microbial antagonism reduce their viability. Understanding how these abiotic, biotic, and anthropogenic drivers shape bacterial persistence provides insight into the ecological resilience of Leptospira and its transmission dynamics. This review underscores the need to coordinate cross-sectoral measures and integrated surveillance linking environmental, animal, and human health through ecologically informed tools such as eDNA and climate-based risk modeling.